Analysis of polymorphic TGFB1 codons 10, 25, and 263 in a German patient group with non-syndromic cleft lip, alveolus, and palate compared with healthy adults - Gressner Axel M; Riediger Dieter; Stoll Doris; Mengsteab Senait; Stoll Christian; Weiskirchen Ralf (BMC, 2004)
Abstract Background Clefts of the lip, alveolus, and palate (CLPs) rank among the most frequent and significant congenital malformations. Leu10Pro and Arg25Pro polymorphisms in the precursor region and Thr263Ile polymorphism in the prodomain of the transforming growth factor β1 (TGF-β1) gene have proved to be crucial to predisposition of several disorders. Methods In this study, polymorphism analysis was performed by real-time polymerase chain reaction (LightCycler) and TGF-β1 levels determined by enzyme-linked immunosorbent assay. Results Only 2/60 Caucasian non-syndromic patients with CLP (3.3%) carried the Arg25Pro and another 2/60 patients (3.3%) the Thr263Ile genotypes, whereas, in a control group of 60 healthy Caucasian blood donors, these heterozygous genotypes were more frequent 16.7% having Arg25Pro (10/60; p < 0.035) and 10,0% having Thr263Ile (6/60), respectively. TGF-β1 levels in platelet-poor plasma of heterozygous Arg25Pro individuals were lower than those of homozygous members (Arg25Arg) in the latter group, but this discrepancy narrowly failed to be significant. Although polymorphisms in codon 10 and 25 were associated with each other, no difference was found between patients and controls concerning the Leu10Pro polymorphism. Conclusions The genetic differences in codons 25 and 263 suggest that TGF-β1 could play an important role in occurrence of CLP, however, functional experiments will be required to confirm the mechanisms of disturbed development.